The Birth of Prophet Muhammad - Khan,Saniyasnain (Goodword book, 2021)
The Birth of Prophet Muhammad (PBUH) is a beautifully illustrated board book that introduces children to the blessed arrival of the final messenger of Islam. It narrates the special events surrounding his birth in Makkah, the joy it brought to the people, and the historical context of the Year of the Elephant. With simple storytelling and soft illustrations, the book highlights the love, mercy, and light associated with his arrival, making it an ideal first step for children learning about the Seerah.
This board book provides a faith-filled and nurturing introduction to the life of Prophet Muhammad (PBUH). It emphasizes love, warmth, and mercy through age-appropriate storytelling while introducing important historical events in a simple way. Designed for little hands, it is a meaningful resource that supports children in building an early spiritual connection with the Prophet.
Toddlers and early learners (under 5 years). Parents and teachers introducing Islamic history in a gentle, age-appropriate way. Islamic libraries, schools, and early childhood learning centers.